Spain : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that after 15 years of impressive growth led by a housing boom, the Spanish economy has entered a sharp downturn in the wake of the global liquidity squeeze since mid-2007. Executive Directors have commended the authorities for their timely and substantial fiscal and financial sector responses to help cushion the downturn. They have emphasized that these efforts need to be complemented by reforms to bolster competitiveness and to avoid a prolonged period of slow growth and high unemployment.